Indonesian Domestic Workers in Taiwan: An International Migration and Workers Rights Perspective - Ujang Komarudin; Pitut Pramuji; Waluyo Handoko; Ida Irawati (APPTHI, 2023)
Abstract. Migration has been a defining aspect of the Asian regional economy for decades. This research delves into the dynamics of Indonesian migrant workers in Taiwan, with a specific emphasis on comprehending the factors contributing to their increasing presence, the living and working conditions they encounter, and the level of legal protection provided by both Indonesia and Taiwan. Employing a combination of qualitative methods and adopting a descriptive analytical approach, the study examines the labor migration patterns and circumstances of Indonesian workers in Taiwan. The findings reveal that Indonesian domestic workers in Taiwan are driven by both “push and pull factors” and the contemporary economics of labor migration. Notably, these factors include better job opportunities and higher wages in Taiwan. However, despite their significant contributions to the host country's economy, both Indonesia and Taiwan fall short in upholding the rights of these workers according to international standards, such as ILO Convention No. 189 on Domestic Workers, adopted in 2011. Nevertheless, this research illustrates the unwavering determination of domestic workers in their quest for improved conditions and acknowledgment, as they collectively challenge discriminatory policies. These findings underscore the pressing need for legal protection, both nationally and in accordance with international conventions like ILO Convention No. 189, which would recognize the labor rights and dignity of domestic workers. Consequently, this study offers valuable insights into the complex landscape of labor migration and the essential role of protective measures in shaping the experiences of Indonesian workers in Taiwan. Keywords: Indonesian migrant workers, Labor migration, Taiwan, Migrant rights, Working conditions Abstrak. Migrasi telah menjadi aspek yang mendefinisikan ekonomi regional Asia selama beberapa dekade. Penelitian ini menggali dinamika pekerja migran Indonesia di Taiwan, dengan penekanan khusus pada pemahaman terhadap faktor-faktor yang berkontribusi terhadap peningkatan kehadiran mereka, kondisi kehidupan dan kerja yang mereka alami, dan tingkat perlindungan hukum yang diberikan oleh Indonesia dan Taiwan. Dengan menggunakan kombinasi metode kualitatif dan mengadopsi pendekatan analitis deskriptif, penelitian ini mengkaji pola migrasi pekerja Indonesia di Taiwan. Temuan menunjukkan bahwa pekerja domestik Indonesia di Taiwan dipengaruhi oleh “faktor dorongan dan tarik” serta dinamika ekonomi migrasi tenaga kerja yang kontemporer. Secara mencolok, faktor-faktor ini mencakup peluang kerja yang lebih baik dan gaji yang lebih tinggi di Taiwan. Namun, meskipun kontribusi signifikan mereka terhadap ekonomi negara tuan rumah, baik Indonesia maupun Taiwan belum mampu menjaga hak-hak pekerja ini sesuai dengan standar internasional, seperti Konvensi ILO No. 189 tentang Pekerja Rumah Tangga, yang diadopsi pada tahun 2011. Namun demikian, penelitian ini mengilustrasikan tekad yang tak tergoyahkan dari pekerja domestik dalam upaya mereka untuk kondisi yang lebih baik dan pengakuan, saat mereka secara bersama-sama menantang kebijakan diskriminatif. Temuan ini menegaskan perlunya perlindungan hukum, baik secara nasional maupun sesuai dengan konvensi internasional seperti Konvensi ILO No. 189, yang akan mengakui hak-hak tenaga kerja domestik dan martabat mereka. Dengan demikian, penelitian ini memberikan wawasan berharga tentang lanskap yang kompleks dalam migrasi tenaga kerja dan peran penting tindakan perlindungan dalam membentuk pengalaman pekerja Indonesia di Taiwan. Kata kunci: Pekerja migran Indonesia, Migrasi tenaga kerja, Taiwan, Hak migran, Kondisi kerja